Análise conceitual sobre intervenção humanitária - Silva, Kevlin Roxani Gualberto da (2022)
When we approach a delicate subject as full of details as human intervention, we are faced with the need to define the terms before developing a comparative work. Therefore, this work presents a conceptual analysis of human intervention. After developing the concepts, they are like proposals that we try to answer the states to establish an intervention. Given this, the work understands what these justifications are and how they are related to the way states relate to the intervention. In addition to disputing the concepts of humanitarian intervention; introduce the states performing involvement in the intervention and the intervention recognized by the UN. We used a theoretical-conceptual method to define the concepts and research of an exploratory nature, using a bibliographic reference and qualitative analysis of documents. We observe that although humanity is also invoked to justify interventions, they do not guarantee the involvement of states, the national ones in a very expressive way. Finally, the study is relevant to contribute to the understanding of the process of human intervention, working this its concepts, the study is relevant. Aiming thus, knowledge for the studies of this area and other studies and development of the subject.